Fundamentals of Entrepreneurship (ENT300) : ZMH Warda Enterprise House of Healin / Sharifah Auni Syamimi Syed Nasir...[et al.] - Syed Nasir, Sharifah Auni Syamimi; Abdullah Muhammad Masyhur Alhaddad, Salma; Shaik Abdul Rani, Nurul Aida Athirah; Zulkhpli, Nurul Izzah; Sulaiman, Nurshafa Farhanim; Akmal Aziz, Nurul Syahirah (2020)
ZMH Warda Enterprise House of Healin started joining Gamat Healin & AG2000 products since 2002 as the only outlet in Alor Setar, Neger Kedah Darul Aman. Until 2005, this company has grown and has been appointed as Konsesi Negeri Kedah Darul Aman by Syarikat Induk Healwell Pharmaceuticals Sdn. Bhd. to expand the market in the Northern Zone of Peninsular Malaysia. Until today, this company is already 6 years old in healthcare and beauty based on Gamat Healin & AG2000 products which are capable and able to grow better in the future. As a result of this company's efforts, now this company already has 18 outlets all over the area under the sponsorship of ZMH Warda Enterprise including 1 outlet in Kangar, Perlis. The company also intends to open another 4 outlets for the purpose of expanding the market and increase sales revenue and make it easier for customers to obtain the product of Gamat Healin & AG2000 simple and pure.